1981
DOI: 10.1111/j.1365-2621.1981.tb04898.x
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Radial Distribution of Specific Gravity Within Potato Tubers

Abstract: A computer program is available which allows the experimentor to examine the radial distribution of specific gravity within individual potato tubers by processing data obtained by peeling tubers concentrically and weighing in air and water between consecutive peelings. The program enables one to calculate optimum estimates of eight parameters of a mathematical model which describes the mean change in specific gravity from the geometric center of a tuber to its periderm. Significant differences in intratuber sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1983
1983
1999
1999

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 1 publication
1
0
0
Order By: Relevance
“…This trend was less marked for the pith. This confirmed results of potato texture studies reported by others (Sharma et al, 1959;Quarmby, 1981; Anzaldúa-Morales and Bourne, 1992; Anzaldúa-Morales et al, 1992).…”
Section: Resultssupporting
confidence: 94%
“…This trend was less marked for the pith. This confirmed results of potato texture studies reported by others (Sharma et al, 1959;Quarmby, 1981; Anzaldúa-Morales and Bourne, 1992; Anzaldúa-Morales et al, 1992).…”
Section: Resultssupporting
confidence: 94%